Investigation of Academic Self Efficacy of University Students in the Sports Area - KOÇAK, Çalık Veli; CANLI, Umut (Asian Journal of Education and Training, 2019)
The purpose of this research; was to investigate the academic self-efficacy of the university students studying in the field of sports according to various variables. The sample group of the study consisted of 386 (female, 42.7% male, 57.3%) volunteer university students who were educated in physical education and sports teaching, sports management and coaching education departments by convenience sampling method. In order to collect the necessary information, a personal information form was used to determine the demographic characteristics of the participants and “Academic Self-Efficacy Scale’’, which was conducted by Ekici (2012) was used for Turkish validity and reliability study. Kolmogorov-Smirnov test was applied to determine whether the data showed normal distribution. In the analysis of the data, independent sample t test was applied according to gender variable. One-Way ANOVA test was used in the analysis of the place where the participants’ grew up, age, university, department, class variables and LSD test was used to determine the significant difference. Pearson Correlation test was used to determine the relationship between academic self-efficacy sub-dimensions and a significant relationship was found. As a result of the study, while there were no differences in terms of gender, age, university and department variables in academic self-efficacy subscales, a significant difference was found in the place where their families lived and class variables. When the results of the study were evaluated; it can be said that demographic variables are not an important factor in academic self-efficacy of the students.